2001
DOI: 10.1007/s11745-001-0755-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of purified pig and human liver retinyl ester hydrolase by pharmacologic agents

Abstract: Identification of inhibitors of retinyl ester hydrolase (REH) would help to elucidate its role in vitamin A metabolism in vivo. By using standard incubation conditions, the effects of 215 drugs as potential inhibitors of purified pig and human liver REH when acting on micellar substrate retinyl palmitate were evaluated at 16.7, 167, and 1670 microM. Out of the compounds tested, 103 were inhibitors of the pig liver enzyme. The most potent compounds, in order of decreasing activity, were chloral hydrate, lovasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Disulfiram [(Et 2 NC(S)S) 2 ], cyanamide (H 2 NCN), aldehydes, and their hydrates (Cl 3 CCHO, CH 3 CHO, and EtCHO) cannot be considered, in a physiological setting, to be specific ALDH2 inhibitors, because most are extensively and rapidly metabolized in vivo; some, including cyanamide, are not ALDH2 inhibitors in vitro. Many are argued themselves to require biotransformation to inhibit ALDH2, and most have been shown to inhibit other sulfhydryl-dependent enzymes, cytochromes P450, and other metalloenzymes (DeMaster et al, 1986(DeMaster et al, , 1998Fleming et al, 1990;Jin et al, 1994;Berndt et al, 1996;Lipsky et al, 2001;Schindler, 2001). Finally, because biomimetic systems have been reported that demonstrate the feasibility of sulfhydryldependent and transition metal-dependent reduction of nitrates to NO (Artz et al, 1996;Murray et al, 2001;, the search should continue for a physiological organic nitrate reduction system that is capable of generating NO and that does not function in nitrate-tolerant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Disulfiram [(Et 2 NC(S)S) 2 ], cyanamide (H 2 NCN), aldehydes, and their hydrates (Cl 3 CCHO, CH 3 CHO, and EtCHO) cannot be considered, in a physiological setting, to be specific ALDH2 inhibitors, because most are extensively and rapidly metabolized in vivo; some, including cyanamide, are not ALDH2 inhibitors in vitro. Many are argued themselves to require biotransformation to inhibit ALDH2, and most have been shown to inhibit other sulfhydryl-dependent enzymes, cytochromes P450, and other metalloenzymes (DeMaster et al, 1986(DeMaster et al, , 1998Fleming et al, 1990;Jin et al, 1994;Berndt et al, 1996;Lipsky et al, 2001;Schindler, 2001). Finally, because biomimetic systems have been reported that demonstrate the feasibility of sulfhydryldependent and transition metal-dependent reduction of nitrates to NO (Artz et al, 1996;Murray et al, 2001;, the search should continue for a physiological organic nitrate reduction system that is capable of generating NO and that does not function in nitrate-tolerant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is thought to express several retinyl ester-splitting enzymes, including REH, that appear genetically, physiologically and biochemically distinct (Harrison, 1998). Because flupenthixol and cefotiam have been shown to inhibit purified liver REH (Schindler, 2001), one might also have expected both agents to inactivate the enzyme in vivo after treatment for 28 d. Surprisingly, the drugs caused an increase in REH activity, suggesting an induction of enzyme protein in these animals. It may be hypothesised that the increased biosynthesis of this hydrolase represents a compensatory mechanism resulting from its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…bile-acid-independent carboxylesterase-4 and bile-acid-dependent retinol ester hydrolase (REH)) (Mentlein & Heymann, 1987;Schindler et al 1998). Of the two retinyl ester-splitting carboxylesterases, it is REH that will receive attention in the present paper, since flupenthixol and cefotiam are known to be in vitro REH inhibitors (Schindler, 2001). The objective of these experiments with BN and LE rats was to investigate the individual effects of flupenthixol and cefotiam on the metabolism of vitamin A in vivo.…”
mentioning
confidence: 99%
“…The following inhibitors were added to their respective incubation mixtures: (1) paraoxonase inhibitors (1 mM EDTA, 0.1 mM HgCl 2 , or 1 mM p ‐OHMB, at the final concentrations in incubations as indicated), (2) reversible esterase inhibitors at 10 or 100 µM (Table 2), or (3) irreversible esterase inhibitors at 1 or 100 µM (Table 2). Inhibitor concentrations that showed clear evidence of inhibition of hydrolysis in published studies were selected 10,22…”
Section: Methodsmentioning
confidence: 99%